Critique of the Neoclassical Economic Model from an Islamic Economic Perspective - Syamsu Rijal; Murphy Xavier; McCarty Elliot (Sharia Oikonomia Law Journal, 2024)
For many years, the neoclassical economic model has been the basis of modern economic analysis. This model is based on the assumptions of individual rationality, market equilibrium, and resource allocation based on market prices. This study examines and evaluates the neoclassical economic model from an Islamic economic perspective. Specifically, it seeks a deeper understanding of how Islamic economic principles and values can offer alternatives or adjustments to the currently dominant neoclassical model. Using a qualitative approach, this study analyzes relevant literature on Islamic and neoclassical economics. In addition, this study involves a comparative study of the basic principles of both paradigms; in addition, this study explores the theoretical and practical perspectives offered by Islamic economists. This study shows that the criticism of the neoclassical economic model from the perspective of Islamic economics has a strong and reasonable basis. Social justice and fair distribution in the distribution of resources are often overlooked by the neoclassical economic model. In conclusion, this study shows that there is great potential to create a more inclusive and sustainable economic model by combining Islamic economic principles with the neoclassical economic framework. Although there are fundamental differences between the two paradigms, incorporating Islamic economic principles in a judicious manner can result in a more equitable and effective economic system.